Analysis of Influencing Factors of Poststroke Depression: Is Higher Body Mass Index Always a Risk Factor of Poststroke Depression?. Issue 3 (March 2019) - Xue, Zhiqiang; Wang, Yanjun; Wang, Lijuan; Shen, Li; Zhang, Anning; Pan, Pan; Wang, Hongjie; Dou, Jing; Guo, Xin; Lv, Yaogai; Jin, Lina; Yao, Yan
Abstract : Abstract: Poststroke depression (PSD) is a common complication of stroke. We sought to investigate the influencing factors of PSD and explored the association between body mass index (BMI) and PSD. A total of 397 stroke patients in a hospital in Qiqihar City, China, were included in this study in 2016. The order of independent variable importance was the score of the National Institute of Health Stroke Scale, frequency of stroke, age, BMI, and sleep duration. Sleep duration of 7 hours or more (compared with <7 hours) was negatively associated with the Self-Rating Depression Scale (SDS) score in all quantiles. BMI of 28.0 kg/m 2 or more (compared with 24.0–28.0 kg/m 2 ) was negatively associated with SDS score, and the coefficients manifested a continuous increasing trend from P 30 to P 84.1 in patients aged 65 years or more. In addition, the relationship between BMI and SDS score demonstrated a "U"-shaped curve in patients aged less than 65 years. The National Institute of Health Stroke Scale score, the frequency of stroke, sleep duration, and BMI were the influencing factors of PSD. BMI played different roles in the two age groups. Abstract : Supplemental digital content is available in the text.